Determination of the Relationship between Healthy Lifestyle Behaviors, Physical Fitness, and Risk Factors of Coronary Heart Diseases in University Students - Ali Ozkan; Mutlu Turkmen; Taner Bozkus; Murat Kul; Recep Soslu; Fatih Yasarturk; Recep Aydin; Umit Oz (MDPI AG, 2018)
The purpose of the present study was to determine the relationship between healthy lifestyle behaviors, physical fitness, and coronary risk factors in university students. 320 male and female (nm: 171; nf: 149, respectively) students from a university participated in this study voluntarily. For the determination of body composition and Body Mass Indexes (BMI), subjects’ height, body weight, and skinfold thickness were taken and body fat percentage (% fat) was determined. Healthy lifestyle behaviors were determined using the healthy lifestyle behaviors questionnaire. Indicators of physical fitness included flexibility (sit-up) (F), muscle strength and endurance (isometric knee (KS), back strength (BS) and a total of shuttle (TS), sprint performance, BMI, and body fat percentage (% fat). Coronary heart disease risk factors included mean arterial blood pressure (systolic (SBP) and diastolic (DBP)), fasting blood levels of triglycerides (TG), total cholesterol (TC), hematocrit (HCT), and hemoglobin (HGB). Results indicated subjects have normal body mass index, body fat percentage, SBP, DBP, TG, TCF, BS, and KS. The results of the Pearson Product Moment Correlation Analysis, indicated that SBP, DBP, TG, TCF, BS, and KS for male and female was significantly correlated with flexibility (sit-up) (F), muscle strength and endurance (isometric knee (KS), back strength (BS) and total of shuttle (TS)), sprint performance. (p < 0.01; p < 0.05), In conclusion, the findings of the present study indicated that physical fitness and healthy lifestyle behaviors play a determinant role in coronary heart disease risk factors for male and female students from a university.